Pengembangan Struktur Ekonomi Jawa Timur pada Tahun 2002 dengan Menggunakan Linear Goal Programming - Santoso, Sugeng; Handayani, Ratri (Department Industrial Engineering, University of Muhammadiyah Malang, 2002)
This research has objective in planning economic structure of East Java in 2002.Some aspect should be considered in planing the structure are consumer demand fulfillment that hasclose relation with output which must be resulted by respective sector,PDRB target achievement while paying attention on problem of absorbing labor force in the respective economic sector and import reduction.To attain the structure we use concept of linear goal programming. The first step we take is developing a model suitable for the linear goal programming and then manipulating data hat is began by aggregation updating,arranging technology coellcient, labor force coefficient,added value coeffcient import coefficient and right side value. To get a solution of the existing model we make use of QS software.From the result of research could be concluced that priority sector must be priority are l. Trading, 2. Textile Industries 3. Transportation4. cigaretteindustry,6. Food of plants.The critical sector have to be attended are 1. Fishery,2. Bevarage industry, 3. Forestry